Os usos do corpo-si no trabalho de transformação de granitos: evidências para saúde e segurança - Thiara De Ângeli Porto; Mônica de Fatima Bianco (Universidade do Porto, 2016)
The ergological analysis is developed, as far as possible, privileging the activity's point of view in order to emphasise the debate about norms and values that renew the human activity on a regular basis. The research took place in a granite processing firm in the State of Espírito Santo, in Brazil. The objective of the research was to understand the body-oneself uses, considering them as taken in the attempt to preserve health and safety, in the humidification processes related to granite treatment. Based on the monitoring of the actual work processes - and assuming the posture of a cartographer, through the exploration of the data collected under the scope of a field diary and in the context of the interviews conducted with ten workers - the study revealed examples of body-oneself uses in the health and safety management, in the activity under analysis. It brought to light the inappropriate resource of the available PPE and the lack of awareness regarding the potential use of the collective protection equipment (CPE), hence compromising the access to dignified working conditions and the preservation of the workers' health and safety.